Amendments of Constitution of Georgia in Attempt to Determine and Resolve the Issues concerning the Status of Autonomous Republics, Separation of Powers and Territorial Arrangement - Zegardeli, Beka (Journal of Law, 2021)
This article discusses the amendments to the Constitution of Georgia relative to attempts to resolve the issues of territorial arrangement. The issues falling into the exclusive competence of the supreme state authorities of Georgia and the so-called "residual powers" are analyzed. Also, the article focuses on the regulations for determining the status of the autonomous republics of Georgia and the separation of powers. It demonstrates the types of problems that existed in the past and the issues that have been resolved in this regard. Ultimately, the presented article highlights the expediency of the emergence of the norms clarifying the Constitution on the issues of territorial arrangement.